Methicillin-Resistant Staphylococcus aureus spa Type t002 Outbreak in Horses and Staff at a Veterinary Teaching Hospital after Its Presumed Introduction by a Veterinarian - Steinman, Amir (J Clin Microbiol, 2015)
Methicillin-resistant Staphylococcus aureus (MRSA) infection and colonization, involving MRSA strains which differ from common human health care-associated clones, have become serious emerging conditions in equine veterinary hospitals. In 2010, MRSA spa type t535 caused an outbreak involving both horses and personnel in a veterinary teaching hospital in Israel. Since then, surveillance continued, and occasional MRSA isolation occurred. Two years later, MRSA of another spa type, t002, was isolated from a veterinarian and, 3 weeks later, from a horse. The appearance of spa type t002, a common clone in human medicine in Israel, among both personnel and horses, prompted a point-prevalence survey of hospital personnel and hospitalized horses. Fifty-nine staff members (n = 16 equine; n = 43, other) and 14 horses were screened. Ten of 59 staff members (16.9%) and 7 of 14 horses (50%) were MRSA carriers. Among the staff, 44% of large animal department (LAD) personnel, compared with only 7% of non-LAD personnel, were carriers. Isolates from all horses and from 9 of 10 personnel were found to be of MRSA spa type t002. This clone was later isolated from an infected postoperative wound in a hospitalized horse. Measures were taken to contain transmission between horses and personnel, as was done in the previous outbreak, resulting in reduction of transmission and, finally, cessation of cross-transmission between horses and personnel.